ANSWERING THE CLIMATE CRISIS BY REDESIGNING SCIENTIFIC BUILDINGS BASED ON THE UNIFICATION OF EPISTEMOLOGY AND AXIOLOGY (A Study of al-Farabi's Philosophy): MENJAWAB KRISIS IKLIM DENGAN MERANCANG ULANG BANGUNAN ILMIAH BERDASARKAN PENYATUAN EPISTEMOLOGI DAN AXIOLOGI (Studi tentang Filsafat al-Farabi) - Istnan Hidayatullah; Kamridah (Department of Islamic Theology and Philosophy, UIN Datokarama Palu, 2025)
Abstract This article explores ideas for addressing the climate crisis by redesigning the structure of knowledge based on the integration of epistemology and axiology from the philosophical perspective of Al-Farabi. This article aims to address gaps in studies regarding the reconstruction of scientific knowledge in the context of confronting the climate crisis from an Islamic philosophical perspective. To date, no research has specifically examined how Al-Farabi’s philosophy contributes to the construction of knowledge grounded in the integration of epistemology and axiology. This article is the result of qualitative research on Al-Farabi’s works as well as other works from journal articles, conference proceedings, books, and online literature discussing the issues of knowledge reconstruction and the climate crisis. Al-Farabi’s views were examined using a descriptive-analytical method with a hermeneutic approach. The research findings indicate that Al-Farabi’s philosophy addresses the issue of unifying epistemology and axiology through the concept of the active intellect (al-aql al-fa’al). Furthermore, Al-Farabi recommends that the study of knowledge be comprehensive, ranging from partial knowledge (juziyat) to universal knowledge (kyulliyat). This recommendation is intended to ensure that the knowledge acquired is holistic rather than merely theoretical. Such holistic knowledge will guide attitudes in practice so that the effects of science do not harm the environment but, on the contrary, help to protect and preserve it. Moreover, Al-Farabi also posits that ethics must be integrated into science. This fusion of holistic knowledge and ethics reflects the unification of the epistemology and axiology of knowledge. This study contributes to the fields of Islamic philosophy, interdisciplinary studies, and contemporary scientific and ecological research..